Forming engineers' sociocultural competence: Engineering ethics at Tomsk polytechnic university; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Galanina E. V. Ekaterina Vladimirovna (Social and humanitarian aspects of engineering, 2015)
Title screen